PENYUSUNAN LEMBAR KERJA PESERTA DIDIK (LKPD) BIOLOGI SMA MELALUI STUDI KEANEKARAGAMAN MAKROFUNGI DI RESOR WAY KANAN BALAI TAMAN NASIONAL WAY KAMBAS - Sutaningsih, Ida; Noor, Rasuane (Bioedukasi Jurnal Pendidikan Biologi, 2015)
Way Kanan Resort is one part of the Way Kambas National Park with an area of ± 40,000 Ha. Way Kanan Resort often found growing makrofungi, but so far no data are reported on a wide macrofungi species and their habitats. The aim of this study was to determine the species and diversity macrofungi  in Way Kanan Resort, and to develop research as a learning resource in the form of LKPD (student sheet) High School Biology Basidiomycota fungus material.This study used purposive sampling method with squared technique. The study was conducted on 26 until January 29, 2015. Data collection macrofungi The Way Kanan Resort area with extensive observations of ± 4 Ha and carried out data collection on 4 squares sampling. As supporting data, performed also a measurement of environmental parameters such as temperature, humidity and pH in each squared. Collecting data about the feasibility of learning resources LKPD measured using a questionnaire expert testing of the presentation material and design LKPD.These results indicate there are 26 species in the macrofungi Way Kanan Resort Way Kambas National Park with the total number of individuals as much as 980 macrofungi. Macrofungi great diversity index using diversity index test ShannonWienner throughout squared observations is 1.345474 with diversity are criteria. Feasibility study source LKPD theoretically has a score of 3-5 on each statement in the questionnaire design and presentation of the material as well as the percentage LKPD vulnerable feasibility has a score of 70% -90% with an average percentage of 80% which indicates LKPD classified as strong criteria. Kata Kunci ; Makrofungi, Resort Way Kanan, student sheets (LKPD)